2021
DOI: 10.2196/31421
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Missing Data With Ecological Momentary Assessment Among People Who Use Drugs: Feasibility Study Using Pilot Study Data

Abstract: Background Ecological momentary assessment (EMA) is a set of research methods that capture events, feelings, and behaviors as they unfold in their real-world setting. Capturing data in the moment reduces important sources of measurement error but also generates challenges for noncompliance (ie, missing data). To date, EMA research has only examined the overall rates of noncompliance. Objective In this study, we identify four types of noncompliance among… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Yet, missingness can occur both due to participant noncompliance (or nonadherence) with study protocols, or due to “technical” failures, including failed prompt delivery/upload, incompatibility of phone operating system, device malfunction, or insufficient service or battery (Heron et al, 2017). Some factors driving missingness in ESM research in youth may be beyond participants’ control; for example, lack of stable cell service or data plan, and smartphone usage restrictions (e.g., parents, school) can drive missingness (Markowski et al, 2021; Santa Maria et al, 2018). In these contexts, missingness should not be characterized as “noncompliance,” and for this reason, we use the umbrella terms “missingness” or “missing data” to capture instances for which data are not available.…”
Section: Experience Sampling and Passive Smartphone Sensor Approaches...mentioning
confidence: 99%
“…Yet, missingness can occur both due to participant noncompliance (or nonadherence) with study protocols, or due to “technical” failures, including failed prompt delivery/upload, incompatibility of phone operating system, device malfunction, or insufficient service or battery (Heron et al, 2017). Some factors driving missingness in ESM research in youth may be beyond participants’ control; for example, lack of stable cell service or data plan, and smartphone usage restrictions (e.g., parents, school) can drive missingness (Markowski et al, 2021; Santa Maria et al, 2018). In these contexts, missingness should not be characterized as “noncompliance,” and for this reason, we use the umbrella terms “missingness” or “missing data” to capture instances for which data are not available.…”
Section: Experience Sampling and Passive Smartphone Sensor Approaches...mentioning
confidence: 99%
“…Although these assessments typically require only a few minutes to complete, participants may nevertheless be unlikely to complete the assessments if they are occupied by a demanding task or activity. Indeed, missing data is a real concern with EMA studies (Markowski et al 2021a). Prospective EMA researchers should therefore carefully consider how many assessments per day they need from each participant.…”
Section: Why (Not) Ecological Momentary Assessments?mentioning
confidence: 99%
“…Indeed, one of the key strengths of the EMA approach lies in its ability to link longstanding sociological theories with methodologically innovative data. Although the increasing profusion of smartphone technology has dramatically increased the feasibility of conducting EMA studies, this approach has rarely been adopted by sociologists due perhaps to the financial and logistical burdens that are associated with the methodology (Keusch and Conrad 2022; Markowski et al 2021a). In this article, I argue that these barriers to entry undersell the relevance of ecological momentary assessments for sociological study.…”
Section: Introductionmentioning
confidence: 99%
“…The major focus of this body of research in the global West has been on various health-based interventions, ranging from drug abuse to mental health and even diabetes (Asgary et al, 2023; Karadzhov, 2023; Markowski et al, 2021). In a study conducted on homeless individuals in the United States, it was found that consistent access to smartphone technology and transportation empowered participants to meet the requirements for the attainment of social needs (Thurman et al, 2021).…”
Section: Dual Barriers To Mobile Phone Access: Gender and Homelessnessmentioning
confidence: 99%